2020
DOI: 10.1101/2020.04.30.20086082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probable causes and risk factors for positive SARS-CoV-2 test in recovered patients: Evidence from Brunei Darussalam

Abstract: We report findings of a national study in Brunei Darussalam indicating that one in five recovered patients subsequently test positive again for SARS-CoV-2-this risk is nearly three times higher in older patients (age 53 and above) than younger ones (below age 53). Review of clinical and epidemiological records do not support reinfection or reactivation as likely causes of the 're-positive' observation. Instead, prolonged but intermittent viral shedding is the most probable explanation. We discuss the implicati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Active SARS-CoV-2 viral replication in the gastrointestinal tract Since strict home quarantine measures precluded the possibility of a new infection, the virus detected in the positive retest was epidemiologically postulated to have been derived from the initial virus infection. 6,[8][9][10][11] However, experimental evidence directly supporting that conclusion has been lacking. We sequenced the viruses obtained from 42 throat and anal samples from 16 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active SARS-CoV-2 viral replication in the gastrointestinal tract Since strict home quarantine measures precluded the possibility of a new infection, the virus detected in the positive retest was epidemiologically postulated to have been derived from the initial virus infection. 6,[8][9][10][11] However, experimental evidence directly supporting that conclusion has been lacking. We sequenced the viruses obtained from 42 throat and anal samples from 16 patients.…”
Section: Resultsmentioning
confidence: 99%
“…This causes public health concerns, such as the origin of the virus in such patients, whether the virus is transmissible, and which patients will have positive retest results. Positive detection of SARS-CoV-2 in discharged patients during follow-up is usually regarded as a recurrence of the original virus after the epidemiological exclusion of a new infection 6,[8][9][10][11] based on the fact that the discharged patients underwent a 14-day home quarantine according to the Chinese government treatment guidelines. However, this postulation has seldom been experimentally supported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the finding is consistent with a report from New York City that revealed that 3.3% of 676 admitted patients aged 65 and over required re-hospitalization, confirming that the risk of readmission is higher in elderly patients than in other age groups [ 16 ]. In the elderly, the response of immune cells against the virus is reduced, so the virus can last longer in the body [ 17 ]. Therefore, there is a possibility that the patients were readmitted because the virus, which remained in the body [ 8 ], could have manifested again with symptoms or been redetected in RT-PCR [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high rate of readmission in the lopinavir/ritonavir group, as indicated above, suggests that the probability of readmission is higher in patients who are older and have underlying diseases. In addition, the high risk of readmission in the lopinavir/ritonavir treatment group, although not statistically significant, has been reported in other studies [ 17 , 31 ], so it is necessary to discuss whether lopinavir/ritonavir is effective in COVID-19 treatment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort form Guangdong, China, 14.5 % (38/262) of convalescent patients from COVID-19 were re-detected to be positive for SARS-CoV-2 during their followed-up period [ 139 ]. Similarly, the data from Brunei Darussalam showed that 19.8 % (21/106) recovered patients were found to be re-positive for SARS-CoV-2 detection [ 140 ]. The re-detectable positive patients were confirmed by RT-PCR tests on anal or nasopharyngeal swabs.…”
Section: Probable Relationship Between the Infection Of Extrapulmonarmentioning
confidence: 99%